Multi-layer growth of tungsten disulphide using thermal chemical vapour deposition. (2023) - Ghanghass, Anjali; Sameera, I.; Bhatia, Ravi
Abstract: Transition metal dichalcogenides, in their 2D form are proven to be significant material for next-generation nanoelectronic and optoelectronic devices. However, for the realization of practical applications, it is very important to devise facile, and cost-effective synthesis routes without compromising their quality. In this work, multi-layer 2D tungsten disulphide (WS2 ) has been synthesized using thermal assisted chemical vapour deposition technique. The synthesis was carried out using two different substrates, and the effect of relative position of tungsten trioxide powder and substrate on the multi-layer growth of WS2 has been studied. The nucleation density and layer number is observed to be varying with the reaction time and the type of the substrate. The as-synthesized samples were characterized by using field emission scanning electron microscopy, and Raman spectroscopy.